Biomorphs: Complex Morphogenesis by a Model Intrinsically Disordered Protein (Small 51/2020). Issue 51 (22nd December 2020) - González‐Obeso, Constancio; González‐Pérez, Miguel; Mano, João F.; Alonso, Matilde; Rodríguez‐Cabello, José Carlos
Abstract : In article number 2005191, José Carlos Rodríguez‐Cabello and co‐workers report micrometric colporate biomorphs self‐assembled from an intrinsically disordered silk‐elastin‐like protein, in which the concurrent effect of hydrophobic, electrostatic and H‐bonding interactions are capable of generating and kinetically trapping complex and transient structures in time during desolvation processes. This platform provides a novel approach to understand the order‐disorder crosstalk and participating interactions in the self‐organization process of native proteins in living organisms and how they develop morphology.